2019
DOI: 10.5010/jpb.2019.46.4.247
|View full text |Cite
|
Sign up to set email alerts
|

Saponarin content and biosynthesis-related gene expression in young barley (Hordeum vulgare L.) seedlings

Abstract: Flavonoids are widely distributed secondary metabolites in plants that have a variety biological functions, as well as beneficial biological and pharmacological activities. In barley (Hordeum vulgare L.), for example, high levels of saponarin accumulate during primary leaf development. However, the effect of saponarin biosynthetic pathway genes on the accumulation of saponarin in barley is poorly understood. Accordingly, the aim of the present study was to examine the saponarin contents and expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…OGT is responsible for the conversion of isovitexin to saponarin in barley [33]. There are two classes of OGT (OGT1 and OGT2) found in the barley genome, where a change in the expression level of OGT1 has been associated with saponarin concentration [11]. In the present study, we found that a positive correlation exists between the HvOGT1 expression pattern and saponarin accumulation, suggesting the possibility of OGT1 involvement in saponarin biosynthesis.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…OGT is responsible for the conversion of isovitexin to saponarin in barley [33]. There are two classes of OGT (OGT1 and OGT2) found in the barley genome, where a change in the expression level of OGT1 has been associated with saponarin concentration [11]. In the present study, we found that a positive correlation exists between the HvOGT1 expression pattern and saponarin accumulation, suggesting the possibility of OGT1 involvement in saponarin biosynthesis.…”
Section: Discussionsupporting
confidence: 62%
“…C-glycosylated flavones constitute the major portion of flavonoids found in barley seedlings [32]. Saponarin (isovitexin-7-O-glucoside) is a major C-glycosylated flavone, which is naturally present in young barley seedlings [11]. Among cellular organelles, saponarin is efficiently stored in vacuoles [33] and high accumulation is typically observed in primary leaves [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations